Pelatihan Asesmen Berbasis Teknologi dan Rubrik Penilaian - Carolina Sri Athena Barus (Jurnal Informasi Pengabdian Masyarakat, 2024)
The Training on Technology-Based Assessment and Rubric Design at SMK Negeri 1 STM Hulu aimed to enhance teachers' competencies in using technology for assessments aligned with the Merdeka Curriculum. This training employed In-Service Training (IST) and On-Service Training (OST) methods, allowing participants to engage in both theoretical and hands-on practice sessions facilitated by AI-based technology such as ChatGPT. The results demonstrated a significant improvement in teachers' understanding and skills, as indicated by higher post-test scores compared to pre-test results. The average post-test score increase highlighted the training's success in boosting digital skills and knowledge related to technology-based assessments. Key challenges included limited infrastructure and initial resistance to change; however, participants' enthusiasm indicated potential for sustainable development. The training recommends further support in terms of infrastructure and continuous guidance to maximize the application of technology in the learning process.